Efeito do suporte social e dos receptores CB1 na consolidação e na extinção da memória de medo condicionado ao contexto - Ferreira, Flávia Fagundes (2017)
Fear memories are the main responsible for the defensive behavior expressed in response to threats, however when manifested recurrently and out of context they may develop serious emotional problems, such as post-traumatic stress disorder (PTSD). These memories can be modulated by pharmacological manipulation in the endocannabinoid system and by interaction with other individuals of the same species in addition to methods such as extinction, clinically known as Exposure Therapy, which aims to inhibit the evocation of a previously acquired memory by overlapping a new one. Therefore, the purpose of this study is to demonstrate the effect of social support on the acquisition and extinction of contextual fear conditioning memory (CFC) under the modulation of subtype 1 cannabinoid receptors (CB1). For this, male adult Wistar rats, with bilaterally implanted cannulae in the CA1 region of the dorsal hippocampus by stereotactic surgery were submitted alone or with the presence of a co-specific to 3 minutes of CFC task training, where they received 3 electrical stimuli of 0.5 mA for 2 seconds and 30 seconds interval between each stimulus. At a 24-hour interval, the animals underwent a 3-minute test session to assay memory acquisition, or a 10-minute extinction session and then the test session to assay memory extinction. Furthermore, immediately after the training session, intra-CA1 infusions of saline (1 μg / μl), the antagonist (AM251, 100 pmol / μl) or the agonist (ACEA, 0.01 fmol / μl) of CB1 receptors were administered. It was found that the presence of a co-specific in the training, extinction or test session induced a significant decrease in the conditioned fear response - measured by the percentage of the animal's immobility time - in all groups, yet even with the expression of memory evocation inhibited by social support, the animals were able to learn the extinction memory. Moreover, a decrease in the conditioned response was observed in the animals receiving both saline and the antagonist infusions, however the greatest effect was observed in the animals receiving agonist infusions, where the inhibition of the response was intensified, presenting the lowest percentages of immobility among all groups. The results obtained in the present study demonstrate the influence of social support on the acquisition and extinction of CFC memory under modulation of CB1 receptors, evidencing its importance on the inhibition of conditioned fear response and facilitation of the memory extinction process, even without the expression of memory evocation along the process.